FORECASTING DEVELOPMENT INDICATORS OF SMALL AND MEDIUM BUSINESS ENTERPRISES - HRYHORUK, Pavlo; ZAVHORODNIA, Tetiana; TKACHENKO, Ivan; KUZ, Arina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers issues related to analyzing the activities of small and medium-sized businesses under martial law. It is established that under such conditions, small and medium-sized enterprises occupy a special place in ensuring the functioning of the domestic economy, acting as one of the primary forms of management and contributing to the processes of demonopolization and privatization. Such enterprises contribute to developing innovative activity, ensuring the market's saturation with goods and services, creating jobs, and forming competition in the market. They are one of the primary sources of income generation for the country. Predictive analytics for small and medium-sized enterprises, in particular, identifying trends in the number of such enterprises and the number of people employed in them, is essential in the strategic planning of their activities. It is established that trend extrapolation models are an effective tool for solving such problems. The article analyzes approaches to modeling the activities of small and medium-sized businesses. It showed various forecasting tools, particularly regression models, production functions, trend extrapolation models, etc. For practical application, the study used trend models that estimate the forecast values of indicators under the complex influence of all factors. The article contains an assessment of the development trends of small and medium-sized businesses, as well as the calculation of forecast values for 2024 for the indicators of the number of enterprises and the number of employees at enterprises, according to which their values are expected to increase. The results obtained during the study and the conclusions formed can be used by state administration bodies, particularly the Khmelnytskyi region, as an analytical basis when reviewing the program of socio-economic development.
Keywords: small and medium-sized enterprises; development trends; forecasting; trend model